Efeito tripanocida de 2-hidroxi-3,4,6-trimetoxiacetofenona isolada de Cotron anisodontus Mull. Arg. em cepa Y de Trypanosoma cruzi - Nascimento, Helaynne Gomes do (2024)
American Trypanosomiasis, popularly known as Chagas disease, is a parasitic infection caused by Trypanosoma cruzi, sometimes neglected, but which has become endemic in developed countries. In the chronic phase, it presents pharmacological therapy with limited and toxic efficacy, making studies necessary in search of therapeutic alternatives. Acetophenones, which have numerous biological properties, become potential molecules in the search for new trypanocidal substances. Therefore, the present study seeks to evaluate the trypanocidal effect of 2-hydroxy-3,4,6-trimethoxyacetophenone (HTMCX) in vitro and in silico on T. cruzi strain Y. The cytotoxicity of the substance in mammalian host cells (LLC-MK2) was evaluated by the MTT reduction assay, with a reduction in CC50 values (concentration capable of reducing cell viability by 50%) observed, when compared to the treated group with Benznidazole (Bz). The evaluation of epimastigote forms was carried out by determining the percentage of viable parasites, HTMCX was able to inhibit cell proliferation (concentration and time dependent) at all concentrations tested (31.2; 62.5; 125; 250; 500; 1000 μM). In the trypomastigote forms, it demonstrated the ability to kill 50% of the parasites (LC50) in the four highest concentrations tested (125, 250, 500 and 1000 μM), with the highest concentration capable of killing around 98.82% of the parasites. When evaluating the relationship between the compound's cytotoxicity for mammalian host cells and the selectivity index (IS: CC50/LC50), the substance showed better selectivity (5.66) when compared to Bz (3.11). HTMCX was able to reduce the percentage of infected cells, as well as the number of intracellular parasites, therefore demonstrating an anti-mastigote effect. Using flow cytometry assays, it was possible to infer possible mechanisms similar to necrosis and cell death, as well as the occurrence of oxidative stress, through increased ROS production and reduced ΔΨm. In docking simulations, HTMCX interacted with trypanothione reductase (TR) residues, which can elucidate the biological effects presented. Thus, it was observed that the molecule under study demonstrated a trypanocidal effect in the tests carried out, as well as a significant reduction in toxicity on host cells. The inhibition of essential parasite enzymes may be related to a possible mechanism of action, evidenced through the induction of cell death mediated by membrane damage and oxidative stress.